Quality of life and people living with AIDS: relationship with sociodemographic and health aspects - Tadeu Lessa da Costa; Denize Cristina de Oliveira; Antonio Marcos Tosoli Gomes; Gláucia Alexandre Formozo (Universidade de São Paulo, 2014)
OBJECTIVE: to analyze the relationship of sociodemographic and health dimensions with the quality of life of people living with the human immunodeficiency virus.METHOD: descriptive and quantitative study. The subjects were 131 seropositive people treated in a specialized center of the Norte-Fluminense municipality, Brazil. A form with sociodemographic and health data was applied, as well as the World Health Organization instrument for the assessment of the quality of life of people with the human immunodeficiency virus.RESULTS: the statistical analysis revealed a significant difference in the assessment of the various dimensions of quality of life by the subjects for gender, education, employment, personal income, medical condition, self-perception of sickness, history of hospitalizations, and bodily alterations due to the antiretroviral drugs.CONCLUSION: professional nursing and health care, as well as public policies in the area, should valorize the quality of life approach, considering the conditions related to its configuration.